Analisis Faktor yang Mempengaruhi Minat Masyarakat terhadap Jual Beli Online dengan Menggunakan Technology Acceptance Model - Miki Wijana (INTERNAL (Information System Journal), 2020)
The use of information technology aims to improve the performance of public services to be more effective and efficient. But problems arise in the Public, for example in e-commerce users or the Olx.co.id website. Problems that arise include the lack of public desire to use technology and (Perceived Usefulness), the technology cannot be fully used by the Public. This study aims to analyze the factors that affect the level of acceptance of the Olx.co.id online buying and selling website by using the Technology Acceptance Model (TAM) framework as a conceptual model. At the beginning of the study, information work was carried out by collecting data from the questionnaire results from 500 respondents as samples and processing them with AMOS 22 software. Then after being processed as a whole, the writer tries to re-process the existing data, but the difference is the separation of the data based on gender respondents (male and female). Thus, a significant relationship will be obtained and can be used as recommendations for improvement for e-commerce websites.